Archetypal Analysis of H. C. Andersen’s The Ugly Duckling: Turning a Loser into a Winner - Anna Toom (IAFOR Journal of Literature & Librarianship, 2023)
The current article is devoted to the study of H. C. Andersen’s fairy tale The Ugly Duckling. The main subject of the study is the fabulous transformation of the tale’s protagonist from a loser into a winner. The research was performed within the archetypal paradigm originated by C. G. Jung (1875–1961). A simplified content analysis of the text was carried out using a set of archetypes composed of elements from the collections of С. Pearson and С. Myss. The study managed to a) identify the archetypal picture that accompanied the protagonist’s sad journey, b) find the key archetypes responsible for his unrelenting motivation to survive and search for a better life, and c) identify the archetypal mechanism of the hero’s transformation from a loser and an outcast into a winner. The results obtained allow us to conclude that Andersen’s fairy tale The Ugly Duckling is valuable from a scientific point of view as a treasure trove of human knowledge and historical experience. This fairy tale has great potential when applied to psychotherapy of trauma and to education, concretely, for work with children who have special needs. Great prospects for its use open up in the workplace, including management and the role training of manufacturers. In our rapidly developing information society, it seems that demand for this fairy tale will only grow.